Age-Dependent Cost-Utility of Pediatric Cochlear Implantation - Semenov, Yevgeniy R. (2013)
OBJECTIVE: Cochlear implantation has become the mainstay of treatment for children with severe-to-profound sensorineural hearing loss (SNHL). Yet, despite mounting evidence on the clinical benefits of early implantation, little data are available on the long-term societal benefits and comparative effectiveness of this procedure across various ages of implantation--a choice parameter for parents and clinicians with high prognostic value for clinical outcome. As such, the aim of the current study is to evaluate a model of the consequences of the timing of this intervention from a societal economic perspective. Average cost-utility of pediatric cochlear implantation by age at intervention will be analyzed. DESIGN: Prospective, longitudinal assessment of health-utility and educational placement outcomes in 175 children recruited from 6 US centers between November 2002 and December 2004, who had severe-to-profound SNHL onset within 1 year of age, underwent cochlear implantation before 5 years of age, and had up to 6 years of post-implant follow-up that ended in November 2008 to December 2011. Costs of care were collected retrospectively and stratified by pre-operative, operative, and post-operative expenditures. Incremental costs and benefits of implantation were compared between the three age groups and relative to a non-implantation baseline. RESULTS: Children implanted at <18 months of age gained an average of 10.7 QALYs over their projected lifetime as compared to 9.0 and 8.4 QALYs for those implanted between 18 and 36 months and at >36 months of age, respectively. Medical and surgical complication rates were not significantly different between the 3 age groups. Additionally, mean lifetime costs of implantation were similar between the 3 groups, at approximately $2,000/child/year (77.5 year life expectancy), yielding costs of $14,996, $17,849, and $19,173 per QALY for the youngest, middle, and oldest implant age groups, respectively. Full mainstream classroom integration rate was significantly higher in the youngest group at 81% as compared to 57% and 63% for the middle and oldest groups, respectively (p<0.05) after six years of follow-up. After incorporating lifetime educational cost savings, cochlear implantation led to net societal savings of $31,252, $10,217, and $6,680 for the youngest, middle, and oldest groups at CI, respectively, over the child’s projected lifetime. CONCLUSIONS: Even without considering improvements in lifetime earnings, the overall cost-utility results indicate highly favorable ratios. Early (<18 months) intervention with cochlear implantation was associated with greater and longer quality of life improvements, similar direct costs of implantation, and economically-valuable improved classroom placement, without a greater incidence of medical and surgical complications when compared to cochlear implantation at older ages.